2023
DOI: 10.1039/d2py01370c
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic catalytic effect of triple dynamic bonds for fast-reprocessing and high-performance cross-linked polymers

Abstract: Dynamic cross-linked polymers (DCPs) are supposed to possess favorable reprocessability and degradability as well as excellent thermal and mechanical properties. However, achieving rapid reprocessing and high performance for DCPs is...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…These results indicated that the reprocessing process did not destroy the thermal mechanical properties of the EPPA CANs. A comparison of the tensile stress, tensile strain, and Young’s modulus of our EPPA CANs with recently reported fast-reprocessable CANs shows that our EPPA CANs exhibit excellent comprehensive properties ,,, ,,, (Figure c).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results indicated that the reprocessing process did not destroy the thermal mechanical properties of the EPPA CANs. A comparison of the tensile stress, tensile strain, and Young’s modulus of our EPPA CANs with recently reported fast-reprocessable CANs shows that our EPPA CANs exhibit excellent comprehensive properties ,,, ,,, (Figure c).…”
Section: Resultsmentioning
confidence: 99%
“…The key to fabricating CANs with a good reprocessing ability is tailoring the dynamic reversibility of dynamic covalent bonds and the mobility of polymer chain segments. Recently, some efforts have been made to realize the fast reprocessing of CANs. , These strategies fall into two main categories. In the first strategy, the exchange kinetics of dynamic covalent bonds are accelerated by adding an extra catalyst, introducing a neighboring group, constructing a dual-dynamic covalent network, or designing new dynamic covalent bonds. ,,,, In 2011, Leibler and co-workers realized the processing of permanently cross-linked epoxies by introducing Zn(Ac) 2 as a catalyst .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it can be concluded that the excellent self-healing ability and re-processable capability of the newly synthesized SWPUA film would prolong its service life, resulting in sustainability via reducing environmental pollution and raw material waste. 34…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it can be concluded that the excellent self-healing ability and re-processable capability of the newly synthesized SWPUA film would prolong its Paper Materials Advances service life, resulting in sustainability via reducing environmental pollution and raw material waste. 34 Biocompatibility evaluation MTT assay. The proliferation of L929 cells on three different concentrations of SWPUA-2 material was analyzed by MTT assay.…”
Section: Materials Advances Papermentioning
confidence: 99%